Initial Experience of 18F-FET PET-MR Image Fusion for Evaluation of Recurrent Primary Brain Tumors - Dadgar, Habibollah; Vafaee, Manouchehr Seyedi; Khorasanchi, Amirreza; Moghadam, Parastoo Kordestani; Nemati, Reza; Shooli, Hossein; Jafari, Esmail; Assadi, Majid (World Journal of Nuclear Medicine, 2023)
Background An accurate monitoring technique is crucial in brain tumors to choose the best treatment approach after surgery and/or chemoradiation. Radiological assessment of brain tumors is widely based on the magnetic resonance imaging (MRI) modality in this regard; however, MRI criteria are unable to precisely differentiate tumoral tissue from treatment-related changes. This study was conducted to evaluate whether fused MRI and O-(2-18F-fluoroethyl)-L-tyrosine (18F-FET) positron emission tomography (PET) can improve the diagnostic accuracy of the practitioners to discriminate treatment-related changes from true recurrence of brain tumor.Methods We retrospectively analyzed 18F-FET PET/computed tomography (CT) of 11 patients with histopathologically proven brain tumors that were suspicious for recurrence changes after 3 to 4 months of surgery. All the patients underwent MRI and 18F-FET PET/CT. As a third assessment, fused 18F-FET PET/MRI was also acquired. Finally, the diagnostic accuracy of the applied modalities was compared.Results Eleven patients aged 27 to 73 years with a mean age of 47 ± 13 years were enrolled. According to the results, 9/11 cases (82%) showed positive MRI and 6 cases (55%) showed positive PET/CT and PET/MRI. Tumoral recurrence was observed in six patients (55%) in the follow-up period. Based on the follow-up results, accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 64, 85, 25, 67, and 50%, respectively, for MRI alone and 91, 85, 100, 100, and 80%, respectively, for both PET/CT and PET/MRI.Conclusion This study found that 18F-FET PET-MR image fusion in the management of brain tumors might improve recurrence detection; however, further well-designed studies are needed to verify these preliminary data.
Keywords: magnetic resonance imaging; positron emission tomography; amino acid PET; brain tumor; 18F-FET PET/CT